Beyond Successful Aging 2.0: Inequalities, Ageism, and the Case for Normalizing Old Ages. (25th March 2020) - Calasanti, Toni; King, Neal
Abstract: This article reviews challenges to Rowe and Kahn's Successful Aging (SA) framework, particularly those that focus on the ways social inequalities, including ageism, stratify age groups and affect possibilities for SA. We then assess the authors' replies to these critiques. We find that SA 2.0 maintains a naturalization of outcomes of age relations, and retains both its focus on personal choice and its indifference to inequalities. We advocate a paradigm shift that recasts the problems of aging in three distinct ways: (i) avoids treating old age as a problem; (ii) avoids treating medical and other maladies as results of aging; and (iii) treats the problems of old age as results of age relations instead. By focusing on age relations, this paradigm goes beyond calls to examine inequalities over the life course, and seeks to normalize old ages, valuing both different modes of aging and old age itself.